(untitled) (Research, Society and Development, 2020)
The objective of the research was to characterize the environment in which the junior companies of a federal institution of higher Education of Amazon (FIHE) are inserted, considering the perceptions of the junior entrepreneurs, tutors, coordinators of the courses of Graduation and the institutional representative linked to the rectory that manages the general actions of the Junior Company Movement. Junior companies exercise an important role in the training of entrepreneurs, as well as bringing students closer to the market. It was found that the relationship between the management of FIHE and the junior companies have many problems related to the organizational structure, process management, physical infrastructure of support and human resources. The junior companies are charged for a more professional posture and dissemination of their activities, the tutors regarding greater effectiveness in support and monitoring, and FIHE in the provision of support infrastructure and training for financial management and legal support. In this context, the main proposal consists of the creation of a nucleus for the acceleration of companies to unite and strengthen the junior company movement in this IFES, with the main responsibility, inspection, disclosure and claims for work infrastructures for companies within the university.